2015
DOI: 10.18805/lr.v0iof.9595
|View full text |Cite
|
Sign up to set email alerts
|

Temperature induction response reveals intrinsic thermotolerant genotypes in soybean

Abstract: The responses of soybean genotypes to high temperature for intrinsic tolerance was studied using Temperature Induction Response (TIR) technique in order identify the genotypes tolerant to high temperature stress. Seven soybean genotypes subjected to lethal and sub lethal temperatures showed significant variation for acquired thermotolerance. Thermotolerant genotypes ADT 1 and CoSoy1 identified by the TIR technique, demonstrated higher survival percentage, and lower growth reduction. Further the tolerant genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…4B). Lower percent reduction of shoot and root growth in tolerant cultivar over control were recorded in soybean as reported by Ange et al (2016). Demir and Kazim (2008) reported that the higher the osmotic stress concentration the lower was the seedling fresh weight of pepper.…”
Section: Effect Of Peg Mediated Drought Stress On Fresh Weight Of Plu...mentioning
confidence: 74%
“…4B). Lower percent reduction of shoot and root growth in tolerant cultivar over control were recorded in soybean as reported by Ange et al (2016). Demir and Kazim (2008) reported that the higher the osmotic stress concentration the lower was the seedling fresh weight of pepper.…”
Section: Effect Of Peg Mediated Drought Stress On Fresh Weight Of Plu...mentioning
confidence: 74%
“…These results are evidenced through the phenotype (Fig 4). The technique of TIR allowed for the identification of genetic variations in these genotypes over a limited timeframe, and the assessment of survival rates provided insights into their tolerance levels toward high temperatures, as demonstrated in this study (Ange et al, 2016;Chandola et al, 2016).…”
Section: (B) Response Of Contrasting Genotypes To Temperature Inducti...mentioning
confidence: 85%
“…This method involves gradually elevating the temperature during the acclimation phase, with the aim of enhancing high-temperature tolerance. This acclimation process is expected to lead to improved survival and growth at elevated temperatures, particularly for the genotypes known for their tolerance (Ange et al, 2016). Notably, the genotypes GE-845 and KMR-630, which had already demonstrated tolerance to osmotic stress, were also found to exhibit tolerance to high-temperature acclimation (Fig 3).…”
Section: (B) Response Of Contrasting Genotypes To Temperature Inducti...mentioning
confidence: 98%